The Roles of Practitioner’s Handling Speech Disorders Children During Endemic - Ahmad Adha Muhamad; Mohammad Azrul Haron; Mohd Nizam Naqiyuddin Ahmad Sobri; Nur Farah Ain Che Soh; Nur Atiqah Liyana Mohd Roziman (Asian TESOL Journal, 2022)
The aim of this research is to get an insight into practitioner views on developing speech disorders among children in Kuantan, Pahang. This is because the practitioner is responsible for handling and educating them in their speech development. The researcher chooses this topic due to the hiking trend in Malaysia where the number of children with speech disorders keeps on increasing from time to time. To make sure that these research objectives come into play, a selected school or centre by the researcher is a place to obtain appropriate data. To find appropriate data to answer the research questions, a selected practitioner who has depth experience, worked at the centre will be interviewed to materialize the aim of this research. Six random samplings have been chosen as respondents which will answer the interview session and forthwith answer research objectives. All of these practitioners are well experienced in handling children with speech delays. Hence, the validity and reliability of the data are considered conclusive methods had been used in comprehensive qualitative research. An interview session will be conducted with selected practitioners who fulfil the standard outlined earlier, such as vast working experience, deep expertise and well experience in handling children with speech disorders and try to obtain as detailed information as possible with is in line with the research objective and research question. For this research, the semi-structured interview is used as it is easier for the researcher to ask an additional question to the participant during the interview session if the researcher is not satisfied with the answer given. This finding from the data analysed successfully answers the research question of getting the information or experience from the practitioner's perspective in conducting children with speech disorders. This result will discuss on most of the practitioners used methods in enhancing children to develop their speech through the method of imitation, reinforcement, and motivation. Other than that, the biggest challenges faced by the practitioners are in understanding children with speech disorder needs and overcoming the challenges.